Essentials of Abdominal Ultrasound - Ali Abdo Gamie, Samia; Mahmoud Foda, Enas (IntechOpen, 2019)
Abdominal ultrasound is a bedside diagnostic tool that helps to discover many abdominal problems. It is a safe and painless procedure that has proven extremely useful for patient workup and diagnosis. This book illustrates the use of ultrasound for all the various organs of the abdomen. Each chapter covers a different organ and presents the latest knowledge and techniques of imaging. The content contained within is relevant across many specialties, including radiology and internal medicine, and is useful for physicians and medical residents and students alike.